Information security governance model to enhance zakat information management in Malaysian zakat institutions - Sulaiman, Hidayah; Jamil, Norziana (Proceedings of the 6th International Conference on Information Technology and Multimedia, 2014)
Zakat or better known as almsgiving is one of the major Islamic principles which is obligated to qualified Muslims. The almsgiving principle aims to assist the needy and eliminate poverty in the society whilst promoting the elimination of greed and selfishness among the Muslim community. The government also holds the responsibility of creating a zakat institution to ensure effective management of the zakat distribution and management. However, due to the growing number of working Muslims and various sources of zakat providers to be managed, this creates an overwhelming amount of information to be carefully managed by the zakat institution and its appointed zakat fund trustee. There exist and information gap when the public demands the zakat institutions to have better transparency in the distribution of zakat especially when various issues are identified with the validity of the zakat information. Hence, there is a need for the zakat institution to have better information security mechanism between the zakat institution and the zakat fund trustee offices. This study proposes an information security governance model for the management of zakat information by testing the correlation between human behavior traits and security governance mechanism with goal congruence and reduction of information asymmetry. The proposed model also aims to provide the zakat institution with a more structured processes of managing the security of the information in order to provide better reporting transparency, making well-informed decisions and instill better trust from the Islamic community with regard to better zakat management and distribution.